Factors influencing green purchase intention in fashion: Environmental knowledge, green marketing, social influence, and eWOM - Yoharis, Brenda; Rahel, Keisha; Lusianah, Lusianah (Edelweiss Applied Science and Technology, 2025)
Understanding the key drivers of environmentally friendly purchasing decisions among younger generations in specific cultural contexts remains limited. In Indonesia, Gen Z represents a big customer segment for sustainable products, but the influence of knowledge, marketing, and social factors on their green purchase intentions is not well established. This study explores how environmental knowledge, green marketing, social influence, and electronic Word-of-Mouth (eWOM) affect Gen Z Indonesian workers’ intentions to purchase eco-friendly fashion products. The aim is to identify which factors hold the strongest influence in shaping purchasing behavior within this demographic. A cross-sectional quantitative method was used, collecting data from 425 Gen Z Indonesian workers aged 15 to 24 through an online survey. The data were analyzed using structural model validation via SmartPLS-4 software. Results show that environmental knowledge and green marketing do not strongly influence green purchase intention. In contrast, social influence and eWOM have a significant positive impact. These findings indicate that interpersonal and digital social dynamics play a greater role than individual knowledge or marketing efforts in driving green consumer behavior among Gen Z Indonesians. From a practical standpoint, sustainable fashion brands targeting this demographic should prioritize influencer marketing, peer-to-peer engagement, and community-driven campaigns over purely informational or traditional marketing approaches. However, the study is limited to a single demographic segment within Indonesia. Therefore, future studies are encouraged to explore these areas further.